Using the Theory of Planned Behavior to predict HPV vaccination intentions of college men. Issue 3 (3rd April 2017) - Catalano, Hannah Priest; Knowlden, Adam P.; Birch, David A.; Leeper, James D.; Paschal, Angelia M.; Usdan, Stuart L.
ABSTRACT: Objective : The purpose of this study was to test Theory of Planned Behavior (TPB) constructs in predicting human papillomavirus (HPV) vaccination behavioral intentions of vaccine-eligible college men.Participants : Participants were unvaccinated college men aged 18–26 years attending a large public university in the southeastern United States during Spring 2015.Methods : A nonexperimental, cross-sectional study design was employed. Instrumentation comprised a qualitative elicitation study, expert panel review, pilot test, test-retest, and internal consistency, construct validity, and predictive validity assessments using data collected from an online self-report questionnaire.Results : The sample consisted of 256 college men, and the final structural model exhibited acceptable fit of the data. Attitude toward the behavior (β = .169) and subjective norm (β = 0.667) were significant predictors of behavioral intention, accounting for 58% of its variance.Conclusions : Practitioners may utilize this instrument for the development and evaluation of TPB-based interventions to increase HPV vaccination intentions of undergraduate college men.